Effect of surface structure on flow and heat transfer using lattice Boltzmann method in a microchannel exchanger. (5th February 2023) - Shao, Baoli; Wang, Shuyan; Chen, Xi; Xie, Lei; Liu, Lili
Graphical abstract: Boundary conditions and contour plots of temperature for structured microchannels. Highlights: D2Q9 and D2Q5 MRT_LB are proposed for flow and heat transfer in microchannel. Effects of four structured surface with micro-bulges on heat transfer are analyzed. The structured surface with rectangular micro-bulges has best thermal efficiency. The optimal ratio of the bulge height to micro-channel height of 0.25 is obtained. The influence of the bulges interval on the heat transfer is less than bulge height. Abstract: The D2Q9 multiple relaxation time (MRT) model and D2Q5 MRT model of lattice Boltzmann method are proposed for the fluid flow and heat transfer in a microchannel exchanger. The appropriate flow and thermal boundary conditions are adopted by non-equilibrium extrapolation method. The performance of heat convection between cold fluid and hot wall in rectangular microchannel is simulated and the results are verified through experiments by Liu et al. and previous numerical results by Ebrahimi et al. Effects of structured surface with rectangular, hemispherical and triangular micro-bulges on the flow behavior and heat transfer of fluid are analyzed. Simulated results indicate that the structured heat transfer surface can effectively enhance the heat transfer, the surface with rectangular micro-bulges for the best performance. Subsequently, the optimal ratio of the micro-bulge height to the micro-channel height of 0.25 is obtained based on the relative Nusselt number of rectangular structured surface, and the Reynolds number decreases with the increase of the micro-bulge height, and the relative logarithmic temperature difference is the opposite. The relative Nusselt number and relative logarithmic temperature difference decrease first and then increase with the increase of micro-bulge distance, while the Reynolds number changes on the contrary. The effect of micro-bulges interval on the heat transfer efficiency is less than that of micro-bulge height, and the thermal efficiency is increased by 15% with an optimal height and distance of the rectangular micro-bumps in the microchannel.